Functional Expression of IP, 5-HT4, D1, A2A, and VIP Receptors in Human Odontoblast Cell Line - Eri Kitayama; Maki Kimura; Takehito Ouchi; Masahiro Furusawa; Yoshiyuki Shibukawa (Biomolecules, 2023)
Odontoblasts are involved in sensory generation as sensory receptor cells and in dentin formation. We previously reported that an increase in intracellular cAMP levels by cannabinoid 1 receptor activation induces Ca2+ influx via transient receptor potential vanilloid subfamily member 1 channels in odontoblasts, indicating that intracellular cAMP/Ca2+ signal coupling is involved in dentinal pain generation and reactionary dentin formation. Here, intracellular cAMP dynamics in cultured human odontoblasts were investigated to understand the detailed expression patterns of the intracellular cAMP signaling pathway activated by the Gs protein-coupled receptor and to clarify its role in cellular functions. The presence of plasma membrane Gαs as well as prostaglandin I2 (IP), 5-hydroxytryptamine 5-HT4 (5-HT4), dopamine D1 (D1), adenosine A2A (A2A), and vasoactive intestinal polypeptide (VIP) receptor immunoreactivity was observed in human odontoblasts. In the presence of extracellular Ca2+, the application of agonists for the IP (beraprost), 5-HT4 (BIMU8), D1 (SKF83959), A2A (PSB0777), and VIP (VIP) receptors increased intracellular cAMP levels. This increase in cAMP levels was inhibited by the application of the adenylyl cyclase (AC) inhibitor SQ22536 and each receptor antagonist, dose-dependently. These results suggested that odontoblasts express Gs protein-coupled IP, 5-HT4, D1, A2A, and VIP receptors. In addition, activation of these receptors increased intracellular cAMP levels by activating AC in odontoblasts.